Uczeń w wirtualnej rzeczywistości - Baran, Aleksandra; Gnat, Marcin; Ausz, Mariusz (Uniwersytet Wrocławski Wydział Nauk Historycznych i Pedagogicznych Instytut Historyczny, 2022)
The article was inspired by problems caused by the transition to distance education, visible in Polish educational institutions. For many years, schools have been paying attention to the negative aspects related to the use of the Internet; access to pornography, social media addiction, FOMO syndrome, cyberbullying, phishing, deepfake, fake, etc. Cyberspace has become a part of the lives of children and teenagers, so teachers should prepare them to use the Internet in a way that will stimulate their development. The curriculum in the digital age must be expanded with issues such as: fake news verification, using mobile applications, being an e-citizen, e-volunteering, as well as obtaining and selecting scientific information from websites. Education in the field of the above topics may result in perception of school among students as a modern entity, able to provide them with both theoretical knowledge and practical skills, allowing them to enter adulthood more easily
Keywords: uczeń w cyberprzestrzeni; edukacja; Internet; korzyści i zagrożenia z sieci; wyzwania współczesnej edukacji